2012
DOI: 10.1111/j.1365-2230.2012.04413.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 genetic polymorphism in Egyptian patients with nonsegmental vitiligo

Abstract: Oxidative stress and accumulation of free radicals might play a role in the pathogenesis of vitiligo. Glutathione S-transferase (GST) is a multigene family of enzymes that detoxify oxidative stress products. In this study, genotyping by multiplex PCR of GSTM1 and GSTT1 in 101 women with nonsegmental vitiligo vulgaris and 101 age-matched healthy female volunteers showed that only the GSTM1 null genotype (P=0.04) was significantly overexpressed in patients with vitiligo. Analysis of the combined effect of GSTM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
(26 reference statements)
0
8
2
Order By: Relevance
“…We were not able to compare our results to the two previous Egyptian reports as, Abd Rabou et al , in 2011 [ 10 ] , did not report such a comparison whereas Bassiouny and Khorshied, in 2013 11 , performed their study with female patients only. Whether our results denote that males and females have different underlying mechanisms leading to their risk of vitiligo, or that it is due to a bias in the selection of cases, or that there was a relatively limited number of patients, is not apparent.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…We were not able to compare our results to the two previous Egyptian reports as, Abd Rabou et al , in 2011 [ 10 ] , did not report such a comparison whereas Bassiouny and Khorshied, in 2013 11 , performed their study with female patients only. Whether our results denote that males and females have different underlying mechanisms leading to their risk of vitiligo, or that it is due to a bias in the selection of cases, or that there was a relatively limited number of patients, is not apparent.…”
Section: Discussioncontrasting
confidence: 62%
“…In the total of 122 patients enrolled in this study, the frequency of the GSTM1/GSTT1 double null genotype was 9.8% while the frequency of GSTM1 null genotype was 52.5% and that of GSTT1 null genotype was 51.6%. The previous Egyptian studies done on vitiligo patients demonstrated 18.8% for GSTM1/T1 double null genotype, 56.4% for GSTM1 null and 30.7% for GSTT1 null 11 and 30% for GSTM1/T1 double null genotype, 52.5% for GSTM1 null and 57.5 % for GSTT1 null. 10…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A decreased expression of MPO, GST, and CAT was reported, and GST polymorphism displayed excess GSTM1 null and GSTT1/GSTM1 double-null type [281, 282]. An involvement of MDF in vitiligo was suggested by altered OXPHOS lipid-dependent subunits [283].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%